Energy management of construction companies on the principles of "Green Economy" - Hlibovets, N. M. (Ways to Improve Construction Efficiency, 2019)
The article reveals the essence of the "green" economy. The well-known features and principles of the green economy, its multiplicative and anti-crisis potential, are highlighted. An understanding of the essence and a description of the goals of "green" technologies is offered, which involves dealing not with the consequences but with the causes of environmental problems. It was identified that among the most important activities for increasing the total benefits for the economy, ecology and employment are the improvement of energy efficiency of buildings and individual structures, construction products and materials, the introduction of renewable energy sources, stable energy efficient transport, agriculture and rational use of water resources. These sectors of the economy can deliver rapid results already in the medium term. The list of market instruments for ensuring the transition of construction to the principles of "green economy" is analyzed, namely :. public and private investments in green production, exchange of eco-technologies, implementation of public procurement policy that stimulates the production of green products, systematic targeted state support for research and development related to the creation of clean technologies, fiscal reforms, introduction of subsidies for environmental protection production and cancellation of subsidies for resource-intensive production, removal of trade barriers for environmental goods and services. The instruments of greening the economy are considered - subsidies, preferential tax rates, grants, adequate control over "green" construction enterprises, reduction of income tax; to give preference to “green products” when conducting public procurement; to facilitate the opening of green production and to simplify the commissioning of enterprises using green production. It is determined that an effective system of environmental taxation, the availability of market financial mechanisms in the field of financing environmental activities are the main components of the "green economy".